A Textual Evaluation of Manhaji by Joko Nursiyo: Insights from Al-Ghali and Abdul Hamid Abdullah’s Standards - Fauzan Fitra Syahrizal; Syofyan Hadi; Asrina Asrina (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study aims to analyze the content of the